Beta Actin Expression Profile in Malignant Human Glioma Tumors - Ghezelbash, Mohsen; Masoudian, Nahid; Pooladi, Mehdi (International Clinical Neuroscience Journal, 2018)
Background: Proteomics is considered a new era in neurophysiological/ neuropathological research including brain tumors. Gliomas which are derived from glial cells are the most common type of brain tumor in humans. Methods: In the present study the total protein content of healthy cells of the brain and brain tumor cells was extracted, purified and quantified by Bradford assay. Two-dimensional electrophoresis were used for protein separation followed by statistical analysis. Primary protein detection was performed based on the differences in isoelectric pH, molecular weight of proteins and protein data banks, which was further confirmed by MALDI-TOF/TOF mass spectrometry (MS). Results: Our results showed elevated levels of beta-actin protein expression in glioma brain tumor cells. It is important to know when a cell is transformed and when it becomes malignant. Here we evaluated the beta-actin expression in malignant cells. Conclusion: Since structural changes are highly involved in tumor cell malignancy, beta-actin elevations can contribute in glioma tumor cell invasiveness.